HUBUNGAN NILAI SOSIAL, BUDAYA dan LINGKUNGAN DALAM MENDUKUNG PARIWISATA BERKELANJUTAN di YOGYAKARTA (Jurnal Ilmiah Pariwisata; Vol 19 No 2 (2014), 2014)
Along with development and economic growth, today increased the role of tourism, as a new sector of substantial foreign exchange earner for the improvement of public welfare. Indonesia as one of the country that has a wealth of outstanding natural and cultural, also enjoy these benefits. However, tourism also often regarded as one of the largest damage contributor to the preservation of the environment and society, particularly through the development of supporting infrastructure. By using approach of quantitative methode, this reserach aims to formulate a model of sustainable tourism-based cultural values, social and environmental wisdom that will support the successful development of tourism in Yogyakarta. Result of this reserach in the field of Environmental Planning is the formulation of the Sustainable Tourism Development Model as a basis for tourism management policies in Yogyakarta in particular and Indonesia in general, as well as the drafting of the new pillars in the ecotourism criteria to complement the pillars that have been there before.
Keywords: Ecotourism, Sustainable Tourism, Tourism Village